Síntese e caracterização de nanocristais semicondutores magnéticos diluídos de Bi2-xCoxS3 em matrizes vítreas - GUIMARÃES, Éder Vinícius (2017)
Diluted magnetic semiconductor nanocrystals of Bi2-xCoxS3 were successfully synthesized and grown in glass matrix of composition 45SiO2.30Na2CO3.5Al2O3.20B2O3 (mol %), doped with precursors Bi2O3, S e Co by means of the fusion-nuclear process and subsequent thermal annealing at a glass transition temperature of 500°C, determined experimentally by differential thermal analysis. Through instrumental methods of analysis and materials characterization techniques was possible evidence of the formation of these nanocrystals. Transmission Electron Microscopy images revealed the size and confirmed the growth of Bi2-xCoxS3 nanocrystals. With the increase of xCo concentration in Bi2- xCoxS3 nanocrystals, occurred to the change in the spacing of the crystalline planes of the characteristic structure of Bi2S3, because of this, nanocrystals x-ray diffraction peaks moved to smaller angles, giving strong evidence of the incorporation of Co2+ ions into the crystalline structure of Bi2S3 nanocrystals. Electron paramagnetic resonance spectra corresponding to electronic transition +½ ↔ -½ evidenced the known octet of hyperfine lines of Co2+ ions when incorporated into Bi2S3 nanocrystals. In the optical absorption spectra, it was possible to follow the growth kinetics of the nanocrystals through the displacement to greater wavelengths ("redshift") of the optical absorption conduction band edge of the quantum dots of Bi2S3 in function of the thermal annealing. This phenomenon resulted in the superposition of the characteristic bands of the d-d transitions of Co2+ ions in the visible region, whose interaction of sp-d exchange between the electrons in the S and Co orbitals of Bi2- xCoxS3 stabilized in tetrahedral symmetry, allowing new optical properties to the semiconductor. Based on crystal field theory with the help of the Tanabe–Sugano diagrams it showed that Co2+ ions were substitutionally incorporated to those of Bi3+ in tetrahedral sites of Bi2S3 nanocrystals, due to the characteristics transitions in the spectral region of the visible and near infrared.